Vakuumska molekularna destilacija - Povh, Bojan (Vakuumist, 2000)
In the last part of this paper problems in designing a small cenrifugal molecular still were studied in detail. Various solutions of basic principles and implements for some important functions are indicated. The attention is given to the design of three most important systems of still apparatus: the transfer of fast rotation in vacuum, the heating of rotor and the liquid transport in molecular still.
Keywords: termodifuzijske operacije; vakuumska tehnika; vakuumska destilacija; molekularna destilacija